Experimental research on saline soil erosion resistance of magnesium phosphate cement pastes. (25th July 2022) - Li, Chaozhong; Zhu, Jincai; Yan, Changwang; Meng, Xiaokai
Graphical abstract: Highlights: The erosion resistance of magnesium phosphate cement slurry to a solution mimicking saline soil was studied. Resistance to saline soil erosion was evaluated by measuring the cement's macro-mechanical properties. The mechanism of resistance to saline soil erosion was studied by microstructural analysis. Abstract: The durability of concrete structures is affected by dry-wet and freeze–thaw cycling, and erosion by saline soils, such as those common to western China. In this study, the anti-erosion properties of magnesium phosphate cement paste (MPC) in salinized soil were investigated. The influences of the magnesium-to-phosphorus ratio (M/P), water-to-cement ratio (W/C), borax-to-magnesium ratio (B/M) and fly ash admixtures were studied in MPC specimens subjected to dry-wet cycle tests in water and saline solutions, with naturally cured specimens used as controls. The compressive strength of MPC was analysed by range analysis, analysis of variance and factor index analysis under various numbers of dry-wet cycles. Mass losses were quantified, morphologies were observed, and X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TG-DSC) were used to assess MPC before and after erosion. It was found that M/P and B/M were the major influences on the compressive strength of MPC. In MPC under natural curing, M/P was a strong influence on strength, while in MPC in water and saline solution, B/M was more important. The MPC slurry was most resistant to saline soil erosion with a 20% fly ash admixture, M/P = 2.5, borax admixture = 0.09 and water-cement ratio = 0.17. After dry-wet cycling, the MPC's mass in water gradually decreased while that in saline solution gradually increased. With 40% fly ash, the compressive strength corrosion resistance coefficient of MPC placed in saline solution for 180 dry-wet cycles was 78.28%, indicating that a moderate amount of fly ash can enhance the saline soil anti-erosion performance of MPC. According to TG-DSC and XRD analyses, when MPC was subject to dry-wet cycling in water, the content of MgKPO4 ·6H2 O(MKP) was the highest. The content was lower under natural curing and lowest in the saline solution. According to SEM, the degree of hydration of MPC was higher under dry-wet cycling than under natural curing, but the crystal structure of MKP was loosely arranged, which reduced the strength of the MPC.